Health disparities in the detection and prevalence of pediatric obstructive sleep apnea - McQuillan, Maureen E.; Jones, Ian C.; Abu Mayyaleh, Haneen F.; Khan, Shajna; Honaker, Sarah M. (Frontiers in Sleep, 2023)
Introduction Pediatric Obstructive Sleep Apnea (OSA) is associated with negative health outcomes, behavior problems, and poor academic performance when left untreated. Prior research has shown that children from racial and ethnic minority backgrounds and those living in lower socioeconomic status (SES) homes or neighborhoods have higher prevalence of OSA but lower likelihood of receiving evidence-based care for OSA. Disparities in pediatric OSA detection (e.g., timely assessment and diagnosis) likely contribute to this observed inequity in receiving treatment. A polysomnogram (PSG) is the gold standard for diagnosing OSA but completing PSG can be challenging. Study aims were to examine racial, ethnic, and SES differences in (1) OSA prevalence and severity and (2) OSA detection, specifically PSG completion rates, timing since referral, and age of diagnosis. Methods Children (aged 1–18, N = 1,860, 56% male) were referred for PSG during a 6-month period. Participants' racial/ethnic background were as follows: 64.8% White non-Hispanic, 23.5% Black non-Hispanic, 9.4% White Hispanic, and 2.4% other. Children predominantly had Medicaid insurance (64.5%). SES was measured by insurance type and neighborhood SES using the Distressed Communities Index (DCI) for each participant's zip code (Economic Innovations Group; https://eig.org/dc). Covariates included child age and sex, BMI, premature birth status, and smoke exposure in the home. Results We replicated previous research by showing that children from minority racial/ethnic backgrounds and lower SES backgrounds had higher prevalence rates of OSA and worse disease severity. Across racial, ethnic, and socioeconomic backgrounds, only 31.6% of the children referred successfully completed PSG. Insurance coverage (Medicaid or private vs. self-pay), was an important factor in predicting earlier timing and better completion rates of PSG, which is essential for successful diagnosis and treatment of pediatric OSA.